The Nonexistence of a Free Entry Cournot Equilibrium in Labor-Managed Economies - Laffont, J. J.; Moreaux, M. (Econometrica, 1983)
[An example is given of a sequence of labor managed economies with decreasing efficiency sizes for which a free entry Cournot equilibrium fails to exist.]